The Urgency Of Sharia Economic Transformation In Facing The Global Economy - Sani, Alfian (LPPM Universitas Terbuka, 2022)
This study discusses the urgency of Islamic Economics's transformation in breaking through the global economy. The research method uses qualitative method and descriptive analysis. The research results indicate that to strengthen Islamic Economics, it must have a strategy that goes beyond the global economy and must be based on sharia principles, referring to the Qur'an and Hadith. The transformation that can be felt now with the presence of the Islamic Economy is the establishment of Islamic Financial Institutions and Islamic Banking which supports the development of the real sector. Islamic economics builds the integrity of Muslims who run the economic wheel under Islamic teachings by adhering to the privileges of Islamic economics itself, namely by avoiding all forms of activities that contain elements of usury which have an impact on harm to others. The challenge faced by the sharia economy is that people still need clarification in understanding the essential characteristics that underlie the sharia banking operational system, namely the profit-sharing system.